FESTSCHRIFT The Institute of Nuclear Medicine 50 Years - University College NHS Foundation Trust and University College London; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
The Institute of Nuclear Medicine, founded in 1961, celebrates with this Festschrift, its Golden Jubilee. It has been a remarkable 50 years of progress of the radionuclide tracer methodology. From initial, physiology based experimentation, a full independent medical discipline evolved, and with it, a comprehensive clinical service. Diagnosis and Treatment with radiotracers have established the basis for Nuclear Medicine. Technological advances have permeated the field like none other, its multidisciplinary character and its translational research are embedded in the history of the Institute and its success. Recent and latest advances in the field promise a future as bright as has been witnessed and documented in the last 50 years.
Keywords: Medicine; Radiology, Medical; Nuclear medicine; Medicine & Public Health; Nuclear Medicine; Imaging / Radiology